It Pays to Manage Health Protection and Safety at Work - Viera Sukalova; Olga Ponisciakova (Communications - Scientific letters of the University of Zilina, 2005)
Under European Union directives, employers have responsibilities for the safety and health of their workers. Directive 89/391 provides the general framework for health and safety management, risk identification and prevention. The directive has been implemented in national legislation that may include additional requirements. In the Slovak Republic the health and safety work act 1996 required an employer to identify and to control risks to workers and others. An assessment of risk is nothing more than a careful examination of what, in work could cause harm to people, so that we can weight up whether wehave taken enough precautions or should do more to prevent harm.